Community-level externalities in child health: Evidence from Sub-Saharan Africa - Emmanuel Skoufias; Katja Vinha (PLoS ONE, 2026)
We use data from twenty countries from the harmonized versions of the Demographic and Health Surveys (DHS) for countries in Sub-Saharan Africa to investigate the extent to which contextual factors such as the level of women’s schooling in the community and the fraction of households in the community with improved water and improved sanitation facilities have an impact on child health in the short-term and in the long-term. Short-term child health is measured by the incidence of reported fever and diarrhea in the two weeks preceding the survey, and long-term child health is measured by child height for age z-scores. We employ the hybrid modeling approach that combines the strengths of random-and fixed-effects models, and considers the role of unobserved heterogeneity at the community level, so far ignored in the literature, to account for all the potential synergies in externalities at the community level. We test the sensitivity of the estimates of externalities to alternative specifications for cluster-level unobserved heterogeneity. The empirical analysis confirms the role of externalities at the community level and shows that the size of these externalities varies between rural and urban areas and by outcome considered. Our results reaffirm the paramount role of externalities in maternal education on child height-for-age and on the incidence of fever and diarrhea in both urban and rural areas. No significant externalities are associated with the fraction of households in the community having improved water, though the fraction of households in the cluster with improved toilets are shown to be significantly associated with a lower probability of fever and diarrhea and improved child height-for-age, with some of these effects varying between urban and rural areas.